Biogeochemical Impacts of a Black Carbon Wet Deposition Event in Halong Bay, Vietnam - Mari, Xavier; Guinot, Benjamin; Thuoc, Chu Van; Brune, Justine; Lefebvre, Jean-Pierre; Angia Sriram, Pradeep Ram; Raimbault, Patrick; Dittmar, Thorsten; Niggemann, Jutta (Frontiers in Marine Science, 2019)
Black carbon (BC) is emitted to the atmosphere during biomass, biofuel and fossil fuel combustion, and leaves the atmosphere via dry or wet deposition on land and on the ocean. On a global scale, wet deposition accounts for about 80% of the total atmospheric BC inputs to the ocean. The input of BC particles to the ocean can enrich surface waters with carbon and associated elements, and owing to high porosity and surface-active properties, BC can alter biogeochemical cycles by sorbing dissolved compounds and promoting aggregation. The rain-mediated input of BC to the ocean and its consequences on nutrient concentrations and particle dynamics were studied in Halong Bay, Vietnam, during a 24 h cycle impacted by short and heavy rainfall events. This study suggests that once introduced in the surface ocean via wet deposition, BC sorbs dissolved organic matter (DOM) and stimulates aggregation processes. The observed wet deposition events were characterized by sudden and pulsed inputs of BC particles that created a thin layer of sinking surface-active aggregates, acting as a net-like scavenger for DOM, nutrients (especially phosphate), and small particles. In addition, the wet deposition events coincided with an enrichment of nutrients in the surface microlayer, with an excess input of nitrogen relative to phosphorus leading to an increase of the molar N:P ratio from 24:1 to 37:1. In the underlying water, the molar N:P ratio also increased (i.e., from 39:1 to 64:1), and this can be attributed to the preferential scavenging of dissolved P-compounds on sinking BC-aggregates.